ヒガシ ナンキョク ウィルクスランド オキ シンカイテイ タイセキブツ ノ シゼン ザンリョウ ジカ ノ トクセイ - 松岡, 東香; マツオカ, ハルカ; 船木, 實; フナキ, ミノル; Matsuoka, Haruka; Funaki, Minoru (2003)
P(論文) 東南極ウィルクスランド沖から採取された深海底堆積物の自然残留磁化(NRM)の特性を明らかにするため,古地磁気・岩石磁気実験が行われた.コア長は540cmである.すべての試料に対し,5mTから100mTまでの段階交流消磁実験を行った.本試料は,他地域における一般的な堆積物の10倍から100倍ものNRM強度を示した.コアの上部460cmでは,大部分の試料が一つの安定な残留磁化成分を持っており,100mTの交流磁場でも消磁できない特異な高安定成分の存在が確認された.これに対し,コア下部では二次磁化を獲得して不安定な消磁曲線を描く試料が多く存在した.全試料に対し詳細な消磁実験を行ったところ,すべての試料の二次磁化が30mTの交流磁場で殆ど消去されていることから,最適消磁レベルは30mTと推定された.最適消磁レベルで消磁したNRMは,本コア試料が三つの地磁気極性を含んでいることを明らかにした.さらに,古地磁気測定に1ccの小型立方サンプルを用いることにより,古地磁気記録の時間分解能を大きく向上させることに成功した.非履歴性残留磁化(ARM)の獲得及び消磁実験を行ったところ,すべての試料が安定なARMを獲得し,その強度もコア一貫して変動が小さいことを確認できた.これは,不安定な残留磁化成分のみを持つ試料が,弱い地球磁場中で残留磁化を獲得した可能性を示唆するものである. Paleomagnetic and rockmagnetic studies were carried out in order to investigate the characteristics of natural remanent magnetization (NRM) of deep-sea sediments cored from offshore Wilkes Land, East Antarctica. The core is 540cm long. Alternating-field (AF) demagnetization experiments using a stepwise AF field from5to100mTwereconductedonallofthesamples. TheNRMintensitiesare10-100 times higher than those commonly obtained from different localities. In the upper 460cm of the core, most samples had stable single component magnetization, and remarkable high-stability components which survived up to 100mT were observed. In the lower section of the core, in contrast, many samples showed more unstable (zigzag) demagnetization curves and secondary acquired magnetizations. The optimum AF demagnetization field intensity was assumed to be 30mT, because the secondary magnetizations of every sample seemed to be completely demagnetized at that AF field. The down core NRM variation after demagnetization by the optimum field revealed that the core contains 3 polarity intervals. By using smaller cubic samples of 1cc volume, the time resolution of the paleomagnetic record was much improved. Anhysteretic remanent magnetization (ARM) experiments were also conducted on all of the samples. The results of the AF demagnetization of ARM imply that the samples showing only soft NRM component possibly acquired their magnetization under a weak ...